The Fabrication of a Highly Sensitive Nano Green Carbon Paste Electrode Modified with Yttrium Doped Manganese Oxide (Mn2O3/Y2O3) for Electrochemical Determination of Marbofloxacin and Its Residues in Bovine Meat and Milk Samples. Issue 10 (25th June 2020) - Abdel-Atty, Shimaa; Abdel-Raoof, Ahmed M.; Mohamed, Tahany F.; Nasr, Zeinab A.; Mohamed, Ghada F.; Elgazzar, Elsayed
Abstract : In the present work, a novel sensitive electrochemical carbon paste electrode chemically modified with yttrium doped manganese oxide Mn2 O3 /Y2 O3 nanostructures was assigned for determination of marbofloxacin (MRB) using square wave voltammetry (SWV) method. MRB has a broad spectrum of bactericidal activity for the treatment of urinary, respiratory and dermatological diseases in bovines and their retention in animal meats and milk leads to adverse side effects for the consumer. Thus a rapid estimation of minor concentrations of MRB has exerted a great concern to ensure food safety. XRD, EDX, Raman spectroscopy, SEM, and TEM techniques were employed to characterize the samples. The electrochemical oxidation behavior of MRB shows irreversible anodic peak at 1.10 V vs Ag/AgCl, in Britton–Robinson buffer (BR) at pH 5.0. The relationship was rectilinear over the range 10 × 10 −9 –1.0 × 10 −4 M between the peak current and its related concentration with a minimum detection limit of 2.4 × 10 −9 M. The developed method was green chemistry challenges and successfully applied to assay the drug in its dosage form, bovine meat and milk samples with a good recovery lies between 94.56% and 105.33% with relative standard deviation less than 10%.